Notes on the distribution of an alien weed Hyptis brevipes (Lamiaceae) in India - Verma, Rohit K; Khan , Bilal A; Wagh, Vijay V; Meena, Baleshwar; Behera , Soumit K; Tamta , Sushma; Chaudhary , Lal. B (Plant Science Today, 2022)
Hyptis brevipes Poit. is a native weed species of South and Central America and has been introduced and naturalized in many parts of SE Asia. It was reported from India for the first time in 1940 from Andaman and Nicobar Islands and then in 2012 from Darjeeling Himalaya. In the present study the authors have noticed the occurrence of the species in the wild in the Dima Hasao district of Assam and the Dampa Tiger Reserve of Mizoram. The study reveals that the species has naturalized in India in some parts of the Northeast region in cultivated lands along roadsides. The detailed taxonomic account of the species along with its distribution, phenology, uses and photographs is provided to confirm its identity and to take stock on its control from its further spread to some other regions, because due to the invasive nature it may affect the growth of crop plants.